2004
DOI: 10.1038/sj.npp.1300404
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Cholinergic Mechanism of Procaine's Limbic Activation

Abstract: The local anesthetic procaine, when administered to humans intravenously (i.v.), yields brief intense emotional and sensory experiences, and concomitant increases in anterior paralimbic cerebral blood flow, as measured by positron emission tomography (PET). Procaine's high muscarinic affinity, together with the distribution of muscarinic receptors that overlaps with brain regions activated by procaine, suggests a muscarinic contribution to procaine's emotional and sensory effects. This study evaluates the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 83 publications
1
18
0
1
Order By: Relevance
“…17,18 Fluorine-18-labelled FP-TZTP has been used to study risk factors of ageing [19][20][21] and mood disorders. 22,23 Driven largely by the theory that M 1 receptor density is altered in the brain of patients with Alzheimer's disease in response to the degeneration of the cholinergic pathway, another TZTP derivative, 3-(4-(hexyloxy)-1,2,5-thiadiazol-3-yl)-1-methyl-1,2,5,6-tetrahydropyridine (xanomeline), was found to exhibit M 1 /M 4 selectivity. 24 While it was found that xanomeline increased cognitive function of patients with Alzheimer's disease, several side effects precluded its therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Fluorine-18-labelled FP-TZTP has been used to study risk factors of ageing [19][20][21] and mood disorders. 22,23 Driven largely by the theory that M 1 receptor density is altered in the brain of patients with Alzheimer's disease in response to the degeneration of the cholinergic pathway, another TZTP derivative, 3-(4-(hexyloxy)-1,2,5-thiadiazol-3-yl)-1-methyl-1,2,5,6-tetrahydropyridine (xanomeline), was found to exhibit M 1 /M 4 selectivity. 24 While it was found that xanomeline increased cognitive function of patients with Alzheimer's disease, several side effects precluded its therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“…Although the IC 50 seems modest (6.3 Ìmol/l), this result does not take into consideration the possibility of a much higher affinity of procaine towards specific subtypes of muscarinic receptors. Moreover, procaine has been recently reported to bind in vivo with a high affinity the M2 receptor located in the paralimbic area of the monkey brain [49]. This affinity for the muscarinic M2 receptor has been presented by these authors to have a role in the emotions and mood modulation which, therefore, could have an interest to treat the non-cognitive conditions which occur during AD.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, lidocaine infused for pain management has been reported to result in dramatic behavioral changes [5]. Procaine, another local anesthetic, is known to have profound selective limbic system activation when administered systemically, which correlates with specific regional blood flow changes in the anterior paralimbic area of the brain [6,7]. As demonstrated on positron emission tomography scan, selective activation of an anterior limbic and paralimbic network in the absence of significant cortical activation is achieved by intravenous procaine infusion and induces "powerful emotional and visceral experiences in healthy subjects" [8].…”
Section: Supraspinal Mechanismsmentioning
confidence: 99%